2009
DOI: 10.1001/archoto.2009.146
|View full text |Cite
|
Sign up to set email alerts
|

Duration-Related Efficacy of Postoperative Antibiotics Following Pediatric Tonsillectomy

Abstract: clinicaltrials.gov Identifier: NCT00662987.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…189 In addition, multiple studies have shown no significant change in pain, emergency room encounters, or hospitalization. 29,[190][191][192][193][194] Any real or theoretical benefit of antibiotics on recovery after tonsillectomy must be balanced against the known risks, harms, and adverse events of therapy. 195 Aside from the direct costs of acquiring the medications, adverse events include rash, allergy, and gastrointestinal upset or diarrhea.…”
Section: Supporting Textmentioning
confidence: 99%
“…189 In addition, multiple studies have shown no significant change in pain, emergency room encounters, or hospitalization. 29,[190][191][192][193][194] Any real or theoretical benefit of antibiotics on recovery after tonsillectomy must be balanced against the known risks, harms, and adverse events of therapy. 195 Aside from the direct costs of acquiring the medications, adverse events include rash, allergy, and gastrointestinal upset or diarrhea.…”
Section: Supporting Textmentioning
confidence: 99%
“…On the other hand, the local prescribing rationale suggests classifying tonsillectomy and adenoidectomy in subgroup A1, i.e., dirty/contaminated surgery and not in A3, i.e., clean surgery (29). Moreover, the use of different surgical techniques and varied access to the resources in a setting also affect the risk of surgical site infections and are a cause of prescribing antibiotics (30). Hence, the present diagnoses-specific study highlights our concern of applicability of available international guidelines, often based on surveillance data of highincome countries, to the other parts of the world especially to the LMICs.…”
Section: Discussionmentioning
confidence: 88%
“…Johnson et al, who analyzed the process of postoperative healing in 49 tonsillectomy patients, comparing the effects of 3-and 7-day prophylactic administration of amoxicillin [13]. Irrespective of the regimen, the antibiotic prophylaxis proved equally effective in terms of the level of pain and the time before returning to a normal diet and physical ac- tivity.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the regimen, the antibiotic prophylaxis proved equally effective in terms of the level of pain and the time before returning to a normal diet and physical ac- tivity. In view of the reduced risk of adverse events, the lower probability of antibiotic resistance and decreased therapeutic costs, this finding justifies a shorter duration of therapy [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation